Economic and War Crimes Courts Could Deepen National Security, Peace and Development in Liberia (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The research reviewed the establishment of War and Economic Crimes Courts as a crucial mechanism to address persisting human security challenges and abuses in Liberia. The aftermath of conflicts left Liberia grappling with numerous challenges, ranging from economic instability to the absence of justice for victims of war crimes and economic crimes. In pursuit of sustainable peace and human security, the establishment of War and Economic Crimes Courts (WECC) for Liberia has been proposed as a mechanism to address the legacies of violence and impunity. This paper reviewed the necessity, feasibility, and potential impact of implementing a WECC in Liberia. This article provides insights into the potential of WECC mechanisms as a catalyst for long-term peace, stability and human security in Liberia. The findings showed that the establishment of War and Economic Crimes Courts for Liberia have the potential to contribute significantly to the country's efforts to achieve enhanced peace, justice, reconciliation, and sustainable development. However, it would require political will, financial resources, and robust institutional support to effectively be implemented. The Government will have to seek support, including funding, technical assistance, and expertise, from the international community to assist with the establishment and functioning of the War and Economic Crimes Courts separately. Also, the Government should collaborate with civil society organizations, international partners, and the public to build consensus on and support for the establishment of the courts for Economic Crimes and War Crimes. This involves conducting awareness campaigns, hosting public forums, and facilitating nationally inclusive dialogue to address concerns and garner backing for the process.